2003
DOI: 10.1046/j.1462-2920.2003.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antibiotics on conjugational resistance gene transfer in Staphylococcus aureus in sewage

Abstract: The growing rate of microbial pathogens becoming resistant to standard antibiotics is an important threat to public health. In order to assess the role of antibiotics in the environment on the spread of resistance factors, the impact of subinhibitory concentrations of antibiotics in sewage on gene transfer was investigated using conjugative gentamicin resistance (aacA-aphD) plasmids of Staphylococcus aureus. Furthermore, the concentration of antibiotics in hospital sewage was measured by high-performance liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 46 publications
3
47
0
3
Order By: Relevance
“…Sim et al (2011) studied the presence of different antibiotics in the effluents of four general hospitals, in Korea, showing that only trimethoprim had higher concentrations (95,100 ng L − 1 ) than those reported in the present study (3963 ng L − 1 ), while ciprofloxacin, sulfamethoxazole and erythromycin showed lower concentrations (up to 3080, 3840 and 470 ng L − 1 , respectively). Moreover, Ohlsen et al (2003) also determined the presence of several antibiotics in the effluent of a university hospital in Würzburg (Germany), reporting concentrations of erythromycin (up to 6000 ng L − 1 ), which are in agreement with the present findings (up to 7545 ng L − 1 in the maternity hospital). Furosemide was the most prevalent diuretic at the four hospitals, being detected at concentrations from 434 ng L − 1 in maternity hospital to 32,558 ng L − 1 in pediatric hospital.…”
Section: Occurrence Of Pharmaceuticals In Hospital Effluentssupporting
confidence: 90%
See 2 more Smart Citations
“…Sim et al (2011) studied the presence of different antibiotics in the effluents of four general hospitals, in Korea, showing that only trimethoprim had higher concentrations (95,100 ng L − 1 ) than those reported in the present study (3963 ng L − 1 ), while ciprofloxacin, sulfamethoxazole and erythromycin showed lower concentrations (up to 3080, 3840 and 470 ng L − 1 , respectively). Moreover, Ohlsen et al (2003) also determined the presence of several antibiotics in the effluent of a university hospital in Würzburg (Germany), reporting concentrations of erythromycin (up to 6000 ng L − 1 ), which are in agreement with the present findings (up to 7545 ng L − 1 in the maternity hospital). Furosemide was the most prevalent diuretic at the four hospitals, being detected at concentrations from 434 ng L − 1 in maternity hospital to 32,558 ng L − 1 in pediatric hospital.…”
Section: Occurrence Of Pharmaceuticals In Hospital Effluentssupporting
confidence: 90%
“…For instance, the measured concentrations of ciprofloxacin are in agreement with previous findings reported in literature to hospital effluents in Norway (up to 23,336 ng L − 1 ) (Thomas et al, 2007), Switzerland (31,980 ng L − 1 ) (Kovalova et al, 2012) and Italy (1400-26,000 ng L − 1 ) (Verlicchi et al, 2012a), while Duong et al (2008) found lower concentrations of ciprofloxacin (1100-10,900 ng L − 1 ) in Taiwan. On the other hand, higher levels were detected in a university hospital in Germany (up to 51,000 ng L − 1 ) (Ohlsen et al, 2003) and in Sweden (3600-101,000 ng L − 1 ) (Lindberg et al, 2004). However, for ofloxacin higher levels were detected in Italy (3300-37,000 ng L − 1 ) (Verlicchi et al, 2012a), USA (up to 35,500 ng L − 1 ) (Brown et al, 2006) and Germany (up to 31,000 ng L − 1 ) (Ohlsen et al, 2003), but not in Sweden (200-7600 ng L − 1 ) (Lindberg et al, 2004).…”
Section: Occurrence Of Pharmaceuticals In Hospital Effluentsmentioning
confidence: 92%
See 1 more Smart Citation
“…The potential of S. aureus to transfer genes encoding antibiotic resistance in wastewater has been shown (Ohlsen et al, 2003). The occurrence and survival of S. aureus in wastewater environments have not been well studied, but the indication from both cultivation and PCR is that S. aureus occurs at low levels in municipal wastewaters and surface waters ( [Schwartz et al, 2003], [Savichtcheva et al, 2007] and [Shannon et al, 2007]).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13]. As a result of their broad usage, these microcontaminants have been detected in concentrations up to several g/L in WWTP effluents and in surface waters.…”
Section: Introductionmentioning
confidence: 99%